Timing of digestion, absorption and assimilation in octopus species from tropical (Octopus maya) and subtropical-temperate (O. mimus) ecosystems - M Linares (Inter-Research, 2015)
Culture of octopuses is still in an experimental stage due to a lack of knowledge about their digestive physiology. This study aimed to determine the temporality of nutrient digestion, absorption and assimilation in 2 species of octopus: the tropical Octopus maya (habitat temperature 22 to 26°C) and the subtropical-temperate O. mimus (15 to 21°C). In both species, the chyme volume displayed 2 peaks over time along the digestive tract: one at the beginning of digestion and a second at the end of the digestion process. These phases were observed in gastric juice (GJ) enzymes, in the flow of nutrients in the digestive gland (DG), in the appearance of metabolites in the hemolymph, and in muscle protein and glycogen levels. The soluble nutrient flow throughout the digestive tract into the DG was similar in both species. However, intracellular digestion was different in O. mimus compared to O. maya; lipids were mobilized faster than proteins in O. mimus, whereas proteins were mobilized faster than lipids in O. maya. This suggests that at low temperatures, the mobilization of lipids could be a biological priority due to their role in membrane protection. In addition, O. mimus displayed more digestive enzyme activity in the GJ and DG compared with O. maya, suggesting that adaptive differences may be related to environmental temperatures.